HPLC ANALYSIS OF RUBIA TINCTORUM AND ITS EFFECT OF METHANOL AND AQUEOUS EXTRACT ON BACTERIA ISOLATED FROM BURNS INFECTION - Aboud, Anmar S (Al-Nahrain Journal of Science, 2010)
This study provides a scientific information about the aqueous and methanol extracts of Rubiatinctorum based on its antimicrobial potential against gram positive and gram negative bacteriaisolated from burns infection using the broth dilution and well diffusion method. Results of thisstudy indicate the presence of many phytochemicals which have antimicrobial activity againstbroad spectrum of bacteria. The methanol extract of R.tinctorum showed highest activity thanaqueous ones. The minimum inhibitory concentration (MIC) of the aqueous extract on the testedorganisms was 25-100mg/ml while in the methanol extract ranged between 25-50mg/ml on thetested organisms and the minimum bacterial concentration (MBC) of the aqueous extract was 25-200 mg/ml while the methanol extract ranged between 25-100 mg/ml. The highest activity ofmethanol extract demonstrated at 100 Co, 121 Co against S.aureus, K.spp, A.hydrophila, andS.marcescens, while there was low activity against S.dysenteria and E.coli. The activity of plantextract increased at acidic pH5-3 whearus, there are slightly increased of plant extract at alkalinepH 8. R.tinctorum contained. essential element (Pb, Na, K, Ca, Fe, Zn, P, Mn, Co and Cu) atdifferent concertation. The high preformance liquid chromatograph (HPLC) analysis of R.tinctorum showed some chemical compounds that have antimicrobial activity against test isolates.The result of this study demonstrate that HPLC analysis of R.tinctorum constituent revealed thathtis plant have antimicrobial activity against test organism and this may be suggest the use at thisextract in treatment of infections disease.